Passive radon monitors with part-time sensitivity to radon. (November 2018) - Pressyanov, Dobromir; Dimitrov, Dimitar; Dimitrova, Ivelina
Abstract: The recent European directive 59/2013 set reference levels for radon at working places. Since usually the personnel spend only part of the day (e. g. 8 h) at work, it is useful to have passive radon monitors that are sensitive only within a certain time window (e. g. the working hours). This work proposes a conceptual design of such a monitor and tests the feasibility of the approach. The design is based on a solid state nuclear track detector (SSNTD) that rotates over a radon absorber during the monitored period of the day. The SSNTD (Kodak Pathe LR-115 type II) has an energy window that makes it insensitive to 222 Rn and 220 Rn progeny plated-out on the surfaces. It only registers alpha particles of the absorbed 222 Rn and its short-lived progeny 218 Po, which is achieved by optimization of the absorber thickness. The absorber construction is further optimized to decrease the inertia of the signal. The modeling and the pilot experimental results show that with a composite absorber consisting of a stack of Makrofol N foils with thickness of less than 7 μm each, the inertia of the signal is less than 20 min. The estimated minimum detectable activity concentration (MDAC) for the proposed 222 Rn monitor is about 15 Bq m −3 for year-long working time exposure (2000 h/year) or 60 Bq m −3 for 3- month exposure period (500 h). Highlights: A new concept for passive radon monitor with part-time sensitivity is proposed. The design involves a SSNTD rotating over a radon absorber/radiator. The design is optimized to ensure low inertia of the signal. The concept feasibility for construction of working place monitors is demonstrated.